Athanasios E. Karathanasis, I Flanginios scholi tis Venetias - Stojanvić, Miodrag (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Αθανάσιος Ε. Καραθανάσης, Η Φλαγγίνειος σχολή της Βενετίας [Flanginios’ School in Venice], Thessaloniki, 1975.